Modified Volume Table for Eucalypts in Haryana - Rawat, J. K. (Indian Forester, 1988)
A modified volume table for Eucalyptus hybrid has been prepared using data from Haryana. This table gives the outputs of timber (stem above 60 cm girth), pulpwood (wood between 60 and 20 cm girth) and fuelwood (small wood below 20 cm girth) expected from a tree of a given girth (over bark at breast height). Its application in making financial valuation of trees and in assessing tbe efficiency of departmental haevesting operations is demonstrated.